Parenting Style and Emotional Intelligence of Late Adolescents Among Psychology Students in Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study aims to determine the relationship between parenting style and emotionalintelligence of late adolescents among psychology students in Bestlink College of thePhilippines. Emotional Intelligence (EI) has an essential role in determining one’s success.Parenting style, on the other hand, has a vital role in the emotional development of theirchildren.The result of this study shows that, the demographic profile of the respondents in terms of age,21 years old placed in rank one as it got the highest percentage of forty-nine point thirty-three(49.33%), while 18 years old got the lowest percentage of one point thirty-three (1.33%). Inaddition, in terms of sex, females are in rank one with a percentage of eighty-two point seven(82.7%), while males got seventeen-point three percent (17.3%). Then, in terms of thedominant parenting style of the respondents’ parents, authoritative is first in rank with a meanof two point eighty-four (2.84), followed by authoritarian with a mean of two point sixty-seven(2.67), and lastly, permissive with a mean of two point sixty-two (2.62). Then, based on thegathered data for emotional intelligence, among the 150 late adolescents from psychologystudents, a composite mean of two point ninety- four (2.94) is calculated with a verbalinterpretation of agree. Finally, in terms of the relationship between parenting style andemotional intelligence, using the Pearson correlation coefficient, the result shows that thecomputed r is 1.00, with an interpretation of a very high correlation. In addition, using thedegree of freedom of 148 and an alpha level of 0.05, the critical value is 0.174.The results of this study imply that the majority of the respondents are 21 years old, while interms of sex, the female got the highest count than males. Then, most of the respondentsconsider their parents to be authoritative, while the permissive parenting style, based on thedata gathered, is the least practiced. In terms of the emotional intelligence of the lateadolescents, based upon looking at the data, most of the respondents’ scores are well withinaverage, and even some of them get high scores, which indicates that the sample populationhas averagely high levels of Emotional Intelligence. Lastly, using Pearson r, the result showsthat there is a significant relationship between parenting styles and emotional intelligence inlate adolescents. Thus, the parenting style might affect the development of the emotionalintelligence of late adolescents.
Keywords: Psychology